Contextualizing Mill’s Idea on Freedom of Expression in The Indonesian Law on Prohibition of Hate Speech - Susanti, Diah Imaningrum (Advances in Social Sciences Research Journal, 2023)
This paper examines John Stuart Mill’s thoughts on freedom of expression as a part of human rights, especially to the extent it is limited by the prohibition of hate speech. Although this right is justified for philosophical, political, and individual reasons, it will be contextualized from Indonesia’s regulations perspectives. Tracing the background to the emergence of freedom of expression and the emergence of hate speech from developed countries such as Europe and America, the background for regulating hate speech is different from that of Indonesia, where hate speech is still regulated and prohibited in various regulations and subject to criminal sanctions. Freedom of expression initiated by John Stuart Mill is not absolute freedom as opinions lose their immunity when the opinions expressed become positive incentives for harmful actions.